SOCIALIZATION OF GIVING GINGER TO REDUCING PATHOGENIC AND FOOD-DESTROYING BACTERIA IN CHICKEN MEAT: SOCIALIZATION OF GIVING GINGER TO REDUCING PATHOGENIC AND FOOD-DESTROYING BACTERIA IN CHICKEN MEAT - Rizky, Vincentia Ade; Siregar, Saadah; Rahayu, Asvia; Krisdianilo, Visensius (JURNAL PENGMAS KESTRA (JPK), 2022)
Broiler chicken meat is a food source of animal origin that is widely consumed in Indonesia. The affordable price makes the demand for broiler chicken meat increasing. Chicken meat is easily contaminated by various microorganisms from the surrounding environment. Several types of microbes that can contaminate meat include E. Coli bacteria, Clostridium botulinum bacteria, Clostridium Perfringens, Salmonella bacteria, Staphylococcus aureus, and Anthrax. Microbial contamination in the form of Salmonella bacteria is generally found in broiler chicken meat. To overcome microbial contamination, the researchers conducted research on the effect of ginger on reducing the number of bacteria in chicken meat. This socialization aims to provide information to the public to be able to use ginger as an inhibitor and reduce the number of pathogenic bacteria and food destroyers in chicken meat. The results of this socialization were obtained from previous research which concluded that a decrease in the number of bacteria was due to the administration of ginger. This is because ginger contains secondary compounds such as phenols, treponoids and benzaldehyde which are bacteriostatic so that they function to inhibit the growth of microorganisms. The results of the socialization carried out in the community around Lubuk Pakam stated that they understood the processing and storage techniques (100%).